Penguatan SistemKeamananGudang Allefix: Evaluasi Kelistrikan dan CCTV - Wibisono, Argo Aflah; suhirwan, suhirwan; Rifandi, Safriudin (J-Eltrik, 2024)
Security of electrical systems and CCTV constitutes a critical aspect in maintaining public safety, particularly amid rising theft cases exploiting infrastructure security gaps. This study aims toevaluate the ef ectiveness of the security system implemented by "Allefix" in protecting electricalinfrastructure and CCTV from theft threats. The methodology includes case studies, field surveys, face-to-face interviews, and descriptive statistical and thematic data analysis. The research findingsprovide a comprehensive overview of existing security system vulnerabilities and yield concreterecommendations for enhancing security ef ectiveness. These findings are expected to make asignificant contribution to the development of more comprehensive and sustainable security policies, particularly in the context of protecting critical infrastructure in Indonesia.